Elastically operating legs - Strategies and construction principles - Seyfarth, A.
In this thesis the mechanisms and advantages of spring-like leg operation were investigated. By examining the long jump the general dynamic was described using a hierarchy of simple models taking salient mechanical and muscle-physiological properties into account.